Pengenalan Huruf Anak Usia Dini Melalui Metode Intervensi Tadika Ceria - Natalia, Fenny; Ngelo, Lourentia Shearly Mahardhika; Tandya, Michael; Savistha, Ni Putu Pradnya Devani; Venissa, Shirley; Setiawan, Yuan Yovita (Bahasa Indonesia, 2024)
This study aims to address the difficulties in letter recognition and enhance the confidence of students aged 3-5 years at TK/KB Al-Ikhlas Surabaya through the "Tadika Ceria" program. This program combines letter games and storytelling to improve students' skills. The research method includes an initial assessment with observations and interviews, followed by the implementation of "Tadika Ceria" over two sessions. The results show an increase in students' ability to recognize letters and their confidence. The assessment and program success indicators demonstrate the effectiveness of "Tadika Ceria." The conclusion highlights the potential of creative and play-based learning methods to improve the effectiveness of letter learning in early childhood education. This program is relevant as an innovation to address the challenges of letter recognition and confidence in kindergarten children. This study contributes to the understanding of learning methods that can be applied in early childhood education. Abstrak Penelitian ini bertujuan mengatasi kesulitan pengenalan huruf dan meningkatkan kepercayaan diri siswa TK/KB Al-Ikhlas Surabaya usia 3-5 tahun melalui program "Tadika Ceria." Program ini menggabungkan permainan huruf dan bercerita untuk meningkatkan keterampilan siswa. Metode penelitian mencakup asesmen awal dengan observasi dan wawancara, diikuti oleh implementasi "Tadika Ceria" selama dua sesi. Hasil penelitian menunjukkan peningkatan kemampuan mengenal huruf dan kepercayaan diri siswa. Asesmen dan indikator keberhasilan program membuktikan efektivitas "Tadika Ceria." Kesimpulan menyoroti potensi metode pembelajaran kreatif dan bermain dalam meningkatkan efektivitas pembelajaran huruf pada anak usia dini. Program ini relevan sebagai inovasi untuk mengatasi tantangan pengenalan huruf dan kepercayaan diri anak TK. Penelitian ini memberikan kontribusi pada pemahaman metode pembelajaran yang dapat diterapkan di pendidikan anak usia dini.